A preliminary snapshot of food contents in the gut of medically important Wall’s Krait (Bungarus walli): an implication for snakebite prevention and snake conservation - Pandey, Deb P.; Piya, Ram C. (Frontiers in Amphibian and Reptile Science, 2025)
IntroductionThe dietary habit of Wall’s Krait (Bungarus walli), which causes several fatalities annually in some South Asian countries, is poorly known. Herein we aim to illustrate the food contents in the gut of preserved B. walli to determine their most favored prey animals.MethodsWe examined the gut contents of three specimens of B. walli preserved in snakebite treatment centers in Jhapa District of Nepal. We identified the contents of their stomachs and intestines. We also collected information on time, date, and geographic locations where people were bitten or encountered these kraits.ResultsAmong the three examined specimens (male/female = 1:2) of B. walli, two kraits had consumed rodents and one had an empty stomach.DiscussionThis is the first study of foods in the guts of B. walli worldwide to our knowledge. The krait specimen having an empty stomach and two specimens with freshly eaten rodents might indicate their access in houses or its outskirts in search of foods. To verify the food stimuli driving them toward human dwellings and the similar feeding but dissimilar distribution patterns of medically important and similar-looking B. walli and common kraits (Bungarus caeruleus), its movement ecology, sexual cycle, and foraging behavior should be documented, and the diet of additional specimens should be studied. However, this preliminary finding could contribute to understand the feeding ecology of this krait intruding into residential areas and to formulate effective prevention strategies against its bite.